HUBUNGAN PEMBELAJARAN TATAP MUKA TERBATAS DENGAN PRESTASI BELAJAR SISWA KELAS TINGGI SDN 9 TA KABUPATEN BONE - Abd Hafid; Muhammad Amran; RIFKAH NURHIDAYAH AFRI (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2023)
This research is a quantitative research with the type of correlational research which aims to determine whether or not there is a significant correlation between limited face-to-face learning and high grade student achievement at SDN 9 TA Kabupaten Bone Based on descriptive statistical analysis the results of limited face-to-face learning with an average of 79,80 are in the very good category and student achievement is obtained an average of 84,35 is in the very good category. Based on inferential statistical analysis, it shows that thitung (3,507) value is greater than (>) ttabel value (1,67655) at the 5% significance level. Therefore H0 rejected and H1 accepted, so that the conclusion of this research is that there is a significant correlation between limited face-to-face learning and high grade student achievement at SDN 9 TA Kabupaten Bone.